PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY, REAL ESTATE, AND BUILD CONSTRUCTION YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Ni Made Suma Sari; Gde Herry Sugiarto Asana (Journal Research of Accounting, 2020)
Financial ratio analysis is one way to calculate financial distress. Financial distress is the result of financial losses experienced by companies, which occurred before bankruptcy or liquidation. Financial distress as dependent variable measured by interest coverage ratio. This is a quantitative research. The data used is secondary data obtained from the Indonesian Stock Exchange in 2016-2018. The population of this research is 88 companies from property, real estate, and build construction listed on Indonesian Stock Exchange in 2016-2018. Based on purposive sampling method, acquired 44 companies that the research sample which increased over 3 years so the total sample in this research was 132 samples. Data analysis technique used is multiple linear regression method. The results of this research are (1) current ratio, return on assets, and total assets turnover have a negative and significant towards financial distress due to the significant of the three independent variables are < α (0.05), while debt to equity ratio has a positive and significant effect on financial distress with significant 0.020 < α (0.05). The analysis shows the regression model Y = 0.592 - 0.334 (X1) + 0.320 (X2) - 0.225 (X3) - 0.031 (X4). The independent variable consisting of current ratio, debt to equity ratio, return on assets, and total asset turnover can explain the financial distress of 32.2%, and the remaining 67.8% is explained by the variables presented in this research.